Effects of a self-affirmation intervention on responses to bowel cancer screening information - Travis, Elizabeth; Ashley, Laura; O'Connor, Daryl B. (Psychology & health, 2025)
To investigate the effect of two brief self-affirmation interventions, immediately prior to reading standard information about bowel cancer screening, on state anxiety, message acceptance and behavioural intention to screen for bowel cancer. 242 adults aged 49 were randomised to one of two self-affirmation interventions (health or values) or one of two control conditions, before reading an NHS England bowel cancer screening leaflet. Participant friend and family history of bowel cancer, state anxiety, message acceptance, behavioural intention to screen, trait self-esteem and spontaneous self-affirmation were measured. Data were analysed using between-participants analysis of variance, planned contrasts and moderated regression. No main effects of experimental condition on levels of state anxiety, message acceptance and behavioural intention were found. However, planned contrasts showed participants who self-affirmed about their health or values (conditions-collapsed) were significantly less anxious and reported significantly higher behavioural intentions compared to participants in the controls (conditions-collapsed). Irrespective of condition, higher levels of spontaneous self-affirmation and trait self-esteem were correlated with lower anxiety, higher intentions, and message acceptance. There was some evidence of the effect of health-based self-affirmation on lowering anxiety; however, further research is needed to explore the effectiveness of different self-affirmation interventions in larger samples.